WNT代谢通路相关基因与中国人群非综合征型唇腭裂发病风险的交互作用 (Beijing Da Xue Xue Bao Yi Xue Ban, 2020)
OBJECTIVE: In this study, we used genome-wide association study (GWAS) data to explore whether WNT pathway genes were associated with non-syndromic oral clefts (NSOC) considering gene-gene interaction and gene-environment interaction. METHODS: We conducted the analysis using 806 non-syndromic cleft lip with or without cleft palate (NSCL/P) case-parent trios and 202 non-syndromic cleft palate (NSCP) case-parent trios among Chinese populations selected from an international consortium established for a GWAS of non-syndromic oral clefts. Genotype data and maternal environmental exposures were collected through DNA samples and questionnaires. Conditional Logistic regression models were adopted to explore gene-gene interaction and gene-environment in teraction using trio package in R software. The threshold of significance level was set as 3.47×10(-4) using Bonferroni correction. RESULTS: A total of 144 single nucleotide polymorphisms (SNPs) in seven genes passed the quality control process in NSCL/P trios and NSCP trios, respectively. Totally six pairs of SNPs interactions showed statistically significant SNP-SNP interaction (P < 3.47×10(-4)) after Bonferroni correction, which were rs7618735 (WNT5A) and rs10848543 (WNT5B), rs631948 (WNT11) and rs556874 (WNT5A), and rs631948 (WNT11) and rs472631 (WNT5A) among NSCL/P trios; rs589149 (WNT11) and rs4765834 (WNT5B), rs1402704 (WNT11) and rs358792 (WNT5A), and rs1402704 (WNT11) and rs358793 (WNT5A) among NSCP trios, respectively. In addition, no significant result was found for gene-environment interaction analysis in both of the NSCL/P trios and NSCP trios. CONCLUSION: Though this study failed to detect significant association based on gene-environment interactions of seven WNT pathway genes and the risk of NSOC, WNT pathway genes may influence the risk of NSOC through potential gene-gene interaction.